Effects of smoking severity and moderate and severe periodontitis on serum C-reactive protein levels: an age- and gender-matched retrospective cohort study. (July 2015) - Azizi, Arash; Sarlati, Fatemeh; Bidi, Mohsen; Mansouri, Leila; Azaminejad, Seyed Mohammad Mehdi; Rakhshan, Vahid
Abstract Background and purpose: C-reactive protein (CRP) which might affect cardiovascular events can be affected by chronic diseases and smoking. Since the effects of smoking dosage as well as the mutual effect of smoking and periodontitis on CRP levels have not been evaluated, we aimed to assess these. Materials and methods: This retrospective age- and gender-matched study was performed on 120 dental patients. Clinical attachment loss, pocket probing depth (PPD), bleeding on probing (BoP), O'Leary plaque index and serum CRP were recorded. Patients were divided into one control and five cohort groups (n = 20 each) according to smoking severity [pack years (PY) below or above 30] and periodontal condition (healthy periodontium and moderate/severe periodontitis). The effects of clinical measurements, age, gender, smoking and periodontitis on CRP were assessed using one- and two-way analyses of variance, Tukey and Bonferroni post hoc tests, and multiple linear regression (α = 0.05). Results: CRP concentrations were 0.07255 ± 0.009539, 0.09645 ± 0.010625, 0.122235 ± 0.018442, 0.3758 ± 0.187369, 0.81595 ± 0.0410299 and 1.8717 ± 0.652728 mg/l, respectively, in the control (PY ≤ 30 with healthy periodontium), cohort 1 (PY > 30 with healthy periodontium), cohort 2 (PY ≤ 30 with moderate periodontitis), cohort 3 (PY > 30 with moderate periodontitis), cohort 4 (PY ≤ 30 with severe periodontitis) and cohort 5 (PY > 30 with severe periodontitis). The positive effects of age, smoking severity, periodontitis and PPD, on CRP increase were significant (Regression p < 0.02). BoP had a negative effect (p = 0.015). Conclusions: Clinicians should warn the patients, especially the older ones, about the effects of their gingival health and smoking on their cardiovascular condition.